2018
DOI: 10.1002/jwmg.21432
|View full text |Cite
|
Sign up to set email alerts
|

Density of American black bears in New Mexico

Abstract: Considering advances in noninvasive genetic sampling and spatially explicit capture-recapture (SECR) models, the New Mexico Department of Game and Fish sought to update their density estimates for American black bear (Ursus americanus) populations in New Mexico, USA, to aide in setting sustainable harvest limits. We estimated black bear density in the Sangre de Cristo, Sandia, and Sacramento Mountains, New Mexico, 2012-2014. We collected hair samples from black bears using hair traps and bear rubs and used a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
23
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 70 publications
9
23
4
Order By: Relevance
“…Capture probability was low for hair traps throughout the project but within the range of similar studies (Murphy et al , Sun et al , Gould et al ), and multiple years of data maintained high precision in density estimates. The low number of spatial recaptures within years in our study suggests that detectors may have been too widely distributed given the size of bear movements in the study areas.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Capture probability was low for hair traps throughout the project but within the range of similar studies (Murphy et al , Sun et al , Gould et al ), and multiple years of data maintained high precision in density estimates. The low number of spatial recaptures within years in our study suggests that detectors may have been too widely distributed given the size of bear movements in the study areas.…”
Section: Discussionsupporting
confidence: 64%
“…As observed in the current study, it is not uncommon for black bear densities to vary widely throughout their range and within individual jurisdictions. Other research also using capture‐recapture techniques reported varying densities in the western United States including New Mexico with 16.5–25.7 bears/100 km 2 (Gould et al ), California with 18–38 bears/100 km 2 (Fusaro et al ), and Montana with 11.4 bears/100 km 2 where black bears were sympatric with grizzly bears ( Ursus arctos ; Stetz et al ). Although there is general consensus that black bear density is likely greater in areas with more natural food availability and less human development (Mace and Chilton‐Radant , Gould et al ), as was seen in the ENC, mixed results have been presented for more urbanized habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mustelids appear to have lower microsatellite amplification rates from scat ( Pekania pennanti, 7–10%; Thompson et al ), compared with ursids (70–80% ( Ursus arctos, Bellemain et al ) or felids (87% for bobcat, Ruell and Crooks ); 63% for mountain lions, Ernest et al ). Hair collected from snares resulted in greater individual amplification; but, in more moist environments, hair snares may require crews to revisit often to reduce environmental exposure (Stetz et al , Gould et al ). When scat amplification rates improve, scent detection teams would increase their utility as a complimentary or alternative technique to hair snares for individual identification.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of genotyping failure on SCR density estimates is functionally similar to randomized subsampling, which SCR models are robust to (Murphy et al, 2016), this still results in the loss of spatial recaptures, which degrades parameter estimate precision while also reducing the efficiency of non-invasive genetic sampling (Augustine et al, 2019;Murphy et al, 2018). As noted for both scat and hair samples collected from other carnivores in the southwestern United States (Gould et al, 2018;Naidu et al, 2011), we suspect that high ultraviolet radiation in the region caused rapid scat decomposition and DNA degradation (Pilliod et al, 2014;Strickler et al, 2015). Survey occasions <7 days in duration may be necessary to combat conditions present in the Southwest; although scat accumulation rates at latrines tend to be slow for otters (Gallant et al, 2007;Rivera et al, 2019), so shorter occasion durations may result in fewer samples collected (Lonsinger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%